Harmonic series with polylogarithmic functions - Stojiljković, Vuk; Fabiano, Nicola; Šešum Čavić, Vesna (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: Some sums of the polylogarithmic function associated with harmonic numbers are established.Methods: The approach is based on using the summation methods.Results: This paper generalizes the results of the zeta function series associated with the harmonic numbers.Conclusions: Various interesting series as the consequence of the generalization are obtained.
Keywords: polylogarithmic function; series; harmonic numbers; integration